Thrips mazandarani sp. n. (Thysanoptera: Thripidae): a new species from the southern coast of the Caspian Sea, Iran - Majid Mirabbalou (نامه انجمن حشره‌شناسی ایران)
A new fern-inhabiting species, Thrips mazandarani sp. n., is described based on two specimens collected from Namak Abrud, Mazandaran province. This is the first thrips reported from fern in Iran. This species is easily distinguished from other 39 Iranian species of the genus Thrips by banded fore wings.